2022
DOI: 10.1136/bmjopen-2021-058952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the development, woman-centricity and psychometric properties of maternity patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs): A systematic review protocol

Abstract: IntroductionWoman-centred care is the right of every woman receiving maternity care, irrespective of where care is being received and who is providing care. This protocol describes a planned systematic review that will identify, describe and critically appraise the psychometric properties of maternity patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs). The woman-centricity of PROM and PREM development and content validation (ie, the extent to which women were involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…CL-PRISS is an ideal tool for schizophrenia patients to report their subjective experience (suffering) induced by the symptoms. Hence, for optimal long-term management of patients with schizophrenia, CL-PRISS and CL-PANSS play pivotal roles in pursuing a better prognosis ( 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…CL-PRISS is an ideal tool for schizophrenia patients to report their subjective experience (suffering) induced by the symptoms. Hence, for optimal long-term management of patients with schizophrenia, CL-PRISS and CL-PANSS play pivotal roles in pursuing a better prognosis ( 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…To rate the quality of the instruments, we will use a modified Grading of Recommendations, Assessment, Development and Evaluations technique defined by the COSMIN guidelines for systematic reviews. The COSMIN guidelines classifies the quality of the evidence into four levels: ‘high’, ‘moderate’, ‘low’ or ‘very low’ 31–33. All appraisals will be made by two researchers independently.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The COSMIN guidelines classifies the quality of the evidence into four levels: 'high', 'moderate', 'low' or 'very low'. [31][32][33] All appraisals will be made by two researchers independently. Disagreements between the researchers will be resolved through discussion, involving a third researcher to resolve disagreements when required.…”
Section: Risk Of Bias (Quality) Assessmentmentioning
confidence: 99%
“…As outlined in Figure 1, initially in Quadrant 1, stakeholders are engaged through information exchange, consultation, and collaboration; and priorities are then agreed on and ranked (including the desired outcomes). Within maternal health care, this could include the co‐identification of women's priority areas for systems change; and the operationalization of women's voices in data collection through the identification and collection of PREMs and PROMs 18 . As an illustrative example, this may include addressing rising cesarean section rates, which has been previously identified as a priority area 19,20 .…”
Section: How To Implement Value the Role Of The Learning Health Systemmentioning
confidence: 99%
“…Within maternal health care, this could include the co‐identification of women's priority areas for systems change; and the operationalization of women's voices in data collection through the identification and collection of PREMs and PROMs. 18 As an illustrative example, this may include addressing rising cesarean section rates, which has been previously identified as a priority area. 19 , 20 In Quadrant 2, relevant research to support these stakeholder‐identified priorities can then be identified by systematic review of research evidence from clinical trials, epidemiology and health economic studies, qualitative and quantitative research.…”
Section: How To Implement Value the Role Of The Learning Health Systemmentioning
confidence: 99%